Bioinformatics Analysis Discovers Microtubular Tubulin Beta 6 Class V (TUBB6) as a Potential Therapeutic Target in Glioblastoma - Jiang, Lan; Zhu, Xiaolong; Yang, Hui; Chen, Tianbing; Lv, Kun (Frontiers in Genetics, 2020)
Glioblastoma (GBM) has long been a major clinical research challenge to scientists. The pivotal role of the mitochondria related gene family in the promotion of GBM tumorigenesis is not clear. We detected that microtubular tubulin beta 6 class V (TUBB6) was one of 33 differentially expressed mitochondrial-focused genes (DEMFGs) in GBM, and considered that TUBB6 is a potential therapeutic target in GBM. TUBB6 was vital for GBM and marked as the key prognostic gene in primary GBM. Mutations of TUBB6 in GBM were rare. Only four TUBB6 co-expressed hub genes (ANXA2, S100A11, FLNA, and MSN) exhibited poorer overall survival rates in higher expression groups (p-value < 0.05). We have confirmed the up-regulation of TUBB6 and its partners, ANXA2 and S100A11 in GBM and validated their importance as prognostic factors in primary GBM. TUBB6 was significantly correlated with stromal score in GBM samples (p-value = 6.99E-04). This study aimed to assess the importance of novel hub genes by analyzing the expression, potential function and prognostic impact of TUBB6 in human primary GBM cancer.